An Analysis of the Effects of North Carolina's Opportunity Scholarship Program on Student Achievement - Anna J. Egalite; D. T. Stallings; Stephen R. Porter (SAGE Publishing, 2020)
The North Carolina Opportunity Scholarship Program is a private school voucher program that provides state-funded vouchers worth up to $4,200 to eligible students entering kindergarten through 12th grade. Because the public and private school sectors administer different assessments, we recruited approximately 700 students to take a common, nationally normed, standardized test. Matching on baseline achievement and rich demographic data, we use a quasi-experimental inverse propensity weighting approach to maximize comparability between the public and private school student samples. Our preferred specification examines first-year effects for new Opportunity Scholarship students, revealing positive estimates of .36 SD in math and .44 SD in language; there is no effect on reading scores. Results for renewal students are statistically significant in language scores only. In further analyses, we estimate separate effects for private schools that regularly administer another version of the assessment used in this study, the Iowa Test of Basic Skills. We conclude by discussing policy implications.